Effects Of Various Treatments On Growth, Vitamin Content, And Catalase Activity In Clitoria Ternatea: A Comparative Study - Manjula A C; Prathibha. K. Y.; Mini M.; Divya Shree G N; Vaishnavi R (Revista Electronica de Veterinaria, 2024)
Clitoria ternatea, commonly known as butterfly pea, is a perennial herbaceous plant belonging to the Fabaceae family.   The present study examines the effects of various treatments viz., Trichoderma viride, Pongamia pinnata, cow dung, Trichoderma agriderma, and Agrimonas on the growth of Clitoria ternatea and the analysis of Vitamin A, Vitamin C, and catalase activity in the treated samples. Clitoria ternatea plants were sourced from Lalbagh Botanical Garden, Bengaluru, and cultivated at Gangodanahalli, Bengaluru. The experiment involved three replicates per treatment, with applications administered two days post-planting and assessments conducted at 30, 60, and 90 days. The results demonstrated that all treatments except Trichoderma agriderma significantly enhanced plant growth. The mixture of all treatments as well as Agrimonas alone, resulted in the greatest increases in shoot and root length, along with a higher number of branches. Pongamia pinnata combined with cow dung promoted shoot length and branch number but reduced root length. Trichoderma viride and Trichoderma agriderma treatments increased branch numbers but reduced root length, with Trichoderma agriderma also decreasing shoot length. Additionally, qualitative and quantitative analysis confirmed the increase in Vitamin A, Vitamin C, and catalase activity in all treated samples. This study highlights the potential of these treatments, particularly Agrimonas, in enhancing the growth of Clitoria ternatea and influencing its antioxidant properties and enzyme activities.